Comparando o efeito de contingência de grupo independente e interdependente sobre o desempenho escolar em matemática - Gois, Nayara de Souza (Universidade Federal de São Carlos, 2021)
The present research replicated studies in social behavior ((Lloyd, Eberhardt & Drake, 1996; Pigott, Fantuzzo, Heggie & Clement, 1984), focusing more specifically on assessing outcomes produced by different group contingencies. Group contingencies are effective in modifying unwanted behaviors and increasing school performance. The aim of the present study was to compare an independent and an interdependent group contingency on the frequency of correctly answering math exercises. Twenty students, both genders, from fourth grade of Elementary School (Cycle 1), from a public school, in a city in the interior of São Paulo, participated in the study. Participants were divided into five groups and each group member performed math exercises with 60 addition and subtraction operations (all exercises were numerical) over a period of ten minutes per session. Reverse designs (ABCA) were used for three groups (Groups 1, 2 and 3), and (ACBA) for the other two groups (Groups 4 and 5). The A condition served as a baseline and no reinforcers were offered. ln B condition, reinforcers were provided by individual performance, required in the group activity. ln condition C reinforcers were provided based on the average performance of the group activity. The results of the present study show that averages of the frequency of correct answers for conditions B and C were higher than for conditions A. However, the participants did not have differences related to means and standard error between conditions B and C.
Comparing the effects of independent and interdependent group contingencies on math performance
Keywords: Contingências de grupo interdependente; Fatos aditivos; Aprendizagem cooperativa; Estudantes do ensino fundamental 1; Independent group contingencies; Additive facts; Cooperative learning; Elementary school students; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::ENSINO E APRENDIZAGEM NA SALA DE AULA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL